Formulation and evaluation of orodispersible tablets of dimenhydrinate by using co-processed superdisintegrants - Ankit, A.; Kumar, G.B. Kiran; Madhu, B.K. (Kathmandu University Journal of Science, Engineering and Technology, 2018)
The main objective of this study was to formulate orodispersible tablets of Dimenhydrinate for quick relief of emesis. Orodispersible tablets were prepared by direct compression method using co-processed super-disintegrants. Co-processed super-disintegrants are the mixture of crospovidone and guar gum in different ratios. The powder mixtures and tablets were subjected to various pre-compression and post-compression evaluations. IR spectroscopy showed no interaction between drug and other excipients. Angle of repose and Carr’s index was found in the range of 23.89°-28.27° and 23.29-15.48 respectively. These results indicated that powder mixtures showed good to acceptable flow properties. All formulations containing co-processed super-disintegrant showed short disintegration time (38.23-17.67 s) and maximum water absorption ratio 73.39%-91.35% compared to control formulation (3.54 min wetting time). Among all formulation F7 containing crospovidone: guar gum in 1:3 ratio showed highest percentage of drug release (98.89%) in 30 min, which is due to high degree of swelling caused by guar gum along with rapid hydration of tablets by crospovidone. Formulation F7 was subjected for 3 months of stability studies; results reviled that the tablet formulation was stable throughout the study period. In conclusion the obtained results suggested that orodispersible tablets of Dimenhydrinate with rapid disintegration and fast drug release can be successfully formulated by employing co-processed super-disintegrants. Kathmandu University Journal of Science, Engineering and Technology Vol. 12, No. I, June, 2016 Page: 23-33